K+ promotes the favorable effect of polyamine on gene expression better than Na. - Takashi Nishio; Kaito Sugino; Yuko Yoshikawa; Michiaki Matsumoto; Yohei Oe; Koichiro Sadakane; Kenichi Yoshikawa (PLoS ONE, 2020)
Background Polyamines are involved in a wide variety of biological processes including a marked effect on the structure and function of DNA. During our study on the interaction of polyamines with DNA, we found that K+ enhanced in vitro gene expression in the presence of polyamine more strongly than Na+. Thus, we sought to clarify the physico-chemical mechanism underlying this marked difference between the effects of K+ and Na+. Principal findings It was found that K+ enhanced gene expression in the presence of spermidine, SPD(3+), much more strongly than Na+, through in vitro experiments with a Luciferase assay on cell extracts. Single-DNA observation by fluorescence microscopy showed that Na+ prevents the folding transition of DNA into a compact state more strongly than K+. 1H NMR measurement revealed that Na+ inhibits the binding of SPD to DNA more strongly than K+. Thus, SPD binds to DNA more favorably in K+-rich medium than in Na+-rich medium, which leads to favorable conditions for RNA polymerase to access DNA by decreasing the negative charge. Conclusion and significance We found that Na+ and K+ exhibit markedly different effects through competitive binding with a cationic polyamine, SPD, to DNA, which causes a large difference in the higher-order structure of genomic DNA. It is concluded that the larger favorable effect of Na+ than K+ on in vitro gene expression observed in this study is well attributable to the significant difference between Na+ and K+ on the competitive binding inducing conformational transition of DNA.